PENGARUH HARGA, PRODUK, PROMOSI DAN DISTRIBUSI TERHADAP KEPUTUSAN PEMBELIAN SUSU NUTRICIA NUTRINIDRINK DI KABUPATEN BARITO UTARA - Boby Saputra (JURNAL ILMU EKONOMI (MANAJEMEN PERUSAHAAN) DAN BISNIS, 2025)
This study aims to analyze the influence of price, product, promotion, and distribution on purchasing decisions of Nutricia Nutrinidrink milk in North Barito Regency. This research uses a quantitative approach with descriptive and verification methods. Data were obtained through questionnaires distributed to consumers who purchased Nutricia Nutrinidrink. The results show that price, product, promotion, and distribution simultaneously have a significant effect on purchasing decisions. Partially, price and distribution have significant effects, while product and promotion have positive but smaller effects. Price is the most dominant factor influencing purchasing decisions. These findings suggest that the company should pay more attention to competitive pricing strategies, expand distribution, and strengthen digital promotion.